Transformasi Konflik Sebagai Konten Bimbingan Kedamaian: Sebuah Tinjauan Literatur - Fahriza, Irfan; Suryahadikusumah, Ahmad Rofi; Lianawati, Ayong; Nadhirah, Nadia Aulia; Nadya, Aisha; Agustina, Ervina Rahma (Universitas Mathla'ul Anwar Banten, 2025)
This study aims to fill the gap in the content of peace guidance services, which are still dominated by normative approaches and do not provide students with transformative conflict management skills. A systematic literature review is the method used in this study to achieve the research objectives, namely formulating dimensions of conflict transformation as the content of peace guidance services. The results of the study indicate that the content of conflict transformation in peace guidance emphasizes awareness of the roots of conflict, creative expression, inclusive dialogue, and commitment to reconciliation. The competencies required include reflective skills, empathetic communication, and cooperation. Arts and creativity-based interventions are suggested to change attitudes and perceptions of conflict.